UJI MEKANIK MATERIAL KOMPOSIT SERAT PINANG - Pathul Hapiz; Aris Doyan; Prapti Sedijani (Jurnal Penelitian Pendidikan IPA, 2018)
The research aim to identify the mechanical properties of  Areca nut fiber composite.. Pinangs fiber composite board uses polyester resin as a binder. Areca nut fiber that used in this research is fiber obtained from pinang which is old and not used anymore. The sample was made by varying the concentration of fiber used (30%, 40%, 50% 60% and 70%). From the results of tests conducted, there are differences in mechanical properties of pine fiber composite material on tensile test and press tests performed. In tensile test, composite of pinang fiber with 50% fiber concentration is the fiber with the best mechanical properties because it has the highest tensile strength, maximum length and maximum load, that is 16.35 MPa, 2.06 mm and 3147.45 N. Meanwhile, Composite betel fiber with a concentration of 30% has the highest broken modulus (MOR) at 30.43 kg / cm2, and elastic module of 1980.2 MPa